Delayed transitions in times of increasing uncertainty: School-to-work transition and the delay of first marriage in Jordan. (December 2016) - Gebel, Michael; Heyne, Stefanie
Highlights: We analyze determinants and changes of the transition to first marriage in Jordan. There is a delay in first marriage for both men and women across cohorts. Effects of education and labor market activities on the transition to first marriage differ between men and women. Education expansion and the decline in public sector jobs can only in part explain the delay of first marriage. Marriage costs and the marriage squeeze do not cause the delay of marriage. Abstract: This paper describes and analyzes determinants and changes of the timing of transition to first marriage in Jordan for four birth cohorts born between 1950 and 1989. Using large-scale, nationally representative life history data from the Jordan Labor Market Panel Survey 2010 and applying event history analyses, we find clear gender differences in marriage patterns and a general trend toward a delay of first marriage in Jordan. Regarding the determinants of individual marriage timing, we find for both men and women that individual education enrollment delays marriage, whereas the effect of the education level is hump-shaped and less pronounced. Inactivity and unemployment delays first marriage for men whereas inactive women experience early marriage. Men and women in public sector jobs make faster transition to first marriage than those in informal jobs. Regarding the changes across cohorts, our results show that the educational expansion partly explains the increasing marriage age of women but not for men. Changes in labor market activities and job quality across cohorts can only in part explain the increasing marriage age in Jordan. Popular explanations that the delay of marriage is caused by rising marriage costs or the marriage squeeze can be rejected.